2015
DOI: 10.1039/c5sc02326b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale interfacial gradients formed by the reactive uptake of OH radicals onto viscous aerosol surfaces

Abstract: The reaction of hydroxyl radicals with viscous oxygenated organic aerosol forms nanometer-sized interfacial gradients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(199 citation statements)
references
References 46 publications
9
188
1
1
Order By: Relevance
“…These reactodiffusive lengths indicate that at all relative humidities HO 2 radicals will be limited to the outermost molecular layers of the particle before reacting away, which is in agreement with the model. Note that it was shown previously that the uptake of gas-phase species generally increases with increasing reacto-diffusive length, which is consistent with our HO 2 uptake coefficient measurements (Slade and Knopf, 2014;Davies and Wilson, 2015;Houle et al, 2015). The red and blue lines in Fig.…”
Section: Ho 2 Uptake By Copper-doped Sucrose Aerosol Particlessupporting
confidence: 80%
“…These reactodiffusive lengths indicate that at all relative humidities HO 2 radicals will be limited to the outermost molecular layers of the particle before reacting away, which is in agreement with the model. Note that it was shown previously that the uptake of gas-phase species generally increases with increasing reacto-diffusive length, which is consistent with our HO 2 uptake coefficient measurements (Slade and Knopf, 2014;Davies and Wilson, 2015;Houle et al, 2015). The red and blue lines in Fig.…”
Section: Ho 2 Uptake By Copper-doped Sucrose Aerosol Particlessupporting
confidence: 80%
“…Organic compounds dissolved within liquid aqueous droplets have been found to be oxidized by gas-phase OH radicals at a much faster rate than within amorphous (semi)solid aerosol particles (Chan et al, 2014;Slade and Knopf, 2014;Davies and Wilson, 2015;Arangio et al, 2015). This is attributed to shorter mixing times in liquid submicron-sized droplets, allowing the condensed-phase material to diffuse rapidly within the droplet bulk and access the surface on the timescale of a reaction Berkemeier et al, 2013Berkemeier et al, , 2016Houle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the reaction with OH radicals, Davies and Wilson (2015) showed that reactions of citric acid (CA) aerosols with OH are slowed when the aerosol assumes a viscous state. The reacto-diffusive length of OH is very small.…”
Section: Atmospheric Outlookmentioning
confidence: 99%
“…As condensed-phase diffusivity is generally expected to be inversely related to viscosity, diffusion coefficients of water, organic molecules and oxidants are essential to understanding the influence of SOA physical state on aerosol processes. Slow diffusivities of organic molecules and oxidants can affect atmospheric chemistry, a point illustrated in a study by Davies and Wilson (2015), who observed the formation of interfacial gradients in the reactive uptake of OH radicals on viscous citric acid (CA) aerosol particles. Whereas particles remained well mixed when dilute, they showed that the surface region affected by the reaction (characterized by the depletion of CA and the formation of reaction products) is a strong function of relative humidity (RH) below 50 %, implying condensed-phase diffusion limitations.…”
Section: Introductionmentioning
confidence: 99%